Influence of environmental factors and diet on inflammatory bowel diseases – a review of the literature - Wesolek, Ewelina; Knop-Chodyła, Kinga; Kochanowska-Mazurek, Anna; Piasecka, Zuzanna; Głaz, Aneta; Pawelec, Karolina; Bielaska, Albert; Jama, Grzegorz (Quality in Sport, 2024)
Introduction and objective Inflammatory bowel disease (IBD), leading to inflammation in the gastrointestinal tract, causes a number of bothersome symptoms that contribute to the deterioration of patients’ quality of life both physically and psychologically. Therapy methods based on pharmacotherapy in IBD often remain insufficient in the treatment of these disorders, so other factors affecting the course of IBD are being sought. The purpose of this review is to present risk and prevention factors for the development of inflammatory bowel disease based on diet and environmental factors. Abbreviated description of the state of knowledge The review has identified a number of factors that influence IBD. One of these is smoking, which shows a commonly detrimental effect on CD, while it has a protective effect in UC patients. Antibiotic therapy, by disrupting the composition of the endogenous intestinal microflora, contributes to an increased risk of IBD exacerbations. A review of the literature on surgical interventions does not allow a clear conclusion. Stress and psychiatric disorders increasing the production of pro-inflammatory cytokines, inhibiting the anti-inflammatory action of the vagus nerve increase the risk of IBD exacerbations. A healthy and balanced diet is an important aspect in the treatment of UC and CD. Scientific societies unanimously recognize breastfeeding and its effect on the development of the intestinal microflora as an important protective factor. On the other hand, introducing an elimination diet without a food intolerance confirmed by a blood test is unjustified and harmful. Summary Awareness of the risk factors for development and exacerbations in IBD patients is crucial. Further research into the impact of diet and environmental factors may support pharmacological treatment in achieving therapeutic success in patients with inflammatory bowel disease.